Pengaruh Kecerdasan Intelektual dan Kecerdasan Emosional terhadap Kinerja Karyawan PT Mitra Ritelindo Lestari Pontianak - Natalia Margareta (MABIS, 2025)
The purpose of this study was to determine whether intellectual intelligence and emotional intelligence influence employee performance at PT Mitra Ritelindo Lestari Pontianak. The entire employee population, totaling 82 people, was sampled. The research employed an associative method. Data collection techniques included questionnaires and literature review. The analysis technique used was quantitative with a Likert scale and SPSS version 23 software. Analytical tools included validity tests, reliability tests, classical assumption tests (normality tests, multicollinearity tests, heteroscedasticity tests, and linearity tests), multiple linear regression tests, coefficient of determination (R2) tests, F tests, and T tests. The results of this study indicate that intellectual intelligence and emotional intelligence partially and simultaneously have a positive and significant effect on employee performance.